Congenital cutis laxa with retardation of growth and development. Issue 9 (September 1987) - Patton, M A; Tolmie, J; Ruthnum, P; Bamforth, S; Baraitser, M; Pembrey, M
Abstract : Seven patients with congenital cutis laxa are presented. The associated features include developmental delay, joint laxity, wide anterior fontanelle, growth retardation, dental caries, and osteopenia. The heterogeneity and inheritance of congenital cutis laxa are discussed. This particular syndrome appears distinct and is likely to be autosomal recessive in view of the two brother-sister sib pairs in this report.